Melasma a monograph - Sarkar, Rashmi; Arora, Pooja; Shehnaz Z Arsiwala; Arya, Latika; Bansal, Shivani; Chowdhury, Joyeeta; L. Datuin, Maria Suzanne; Pandya, Amit G. (India : Jaypee Brothers Medical Publisher, 2015)
A monograph on melasma was the first book I had in mind when I thought of writing. However, it stayed in the shelves of my mind quietly, till I co-edited two others books.
Contents Contributors Foreword Preface Epidemiology and Global Distribution of Melasma Nokubonga Khoza, Ncosa Dlova, AnisaMosam 2. Etiological Factors and Triggering Factors Hee Young Kang 3. Etiopathogenesis of Melasma Sidharth Santhalia 4. Clinical Features and Classification of Melasma, Wood's Lamp, and Melasma Area Severity Index Score Nilendu Sarma, Joyeeta Chowdhury 5. Investigations in Melasma: Histopathology, Dermoscipy, and In Vivo Reflexctance Confocal Microscopy in Melasma Hee Young Kang 6. Investigations in Melasma: Dermoscopy in Melasma Saloni Katoch 7. Photoprotection and cosmetic camouflajge for melasma Narenda Gokhale Y otros sietes capítulos más Appendix: Treatment Algorithm for melasma
Incluye Contents
Incluye Appendix
Keywords: MELASMA; EPIDEMIOLOGY